Application of Thick Concrete Rolling Technology in Gaobei Water Conservancy Project of Han River - SHI Aijun; WANG Yongjian; DING Shihui; LI Ke; XIE Xiangming; ZENG Licheng; YAO Chukang (Renmin Zhujiang)
In order to increase the thickness of roller compacted concrete (RCC) from the conventional 30 cm to 50~60 cm,and improve the construction efficiency of RCC dams,this paper conducts the 50~60 cm concrete rolling compaction test by the first domestic double-steel-wheel vertical vibratory roller and compaction detector,determines the best construction parameters through this test and applies them in the Gaobei Water Conservancy Project of Han River.The test results show that,by reasonable selection of the rolling parameters,the domestic double-steel-wheel vertical vibratory roller is capable of compacting concrete with a thickness of 60 cm and below.While the domestic compaction detector can detect the compactness of concrete with a thickness of 60 cm and below.Thick concrete rolling technology,which can increase construction speed of dams and reduce the number of interlayer bonding surfaces of the dam,show a good popularization and application in construction of RCC dams.